Respuesta :

Step-by-step explanation:

We know that

[tex]\boxed{\sf a^m\times a^n=a^m+n}[/tex]

[tex] \sf \: {8}^{5} \times {8}^{6} \\ \sf \leadsto \: {8}^{5 + 6} \\ \sf \leadsto {8}^{11} [/tex]

[tex]\sf More\;to\: know{\begin{cases}\bf{\dag}\:\:\underline{\text{Law of Exponents :}}\\\\\bigstar\:\:\sf\dfrac{a^m}{a^n} = a^{m - n}\\\\\bigstar\:\:\sf{(a^m)^n = a^{mn}}\\\\\bigstar\:\:\sf(a^m)(a^n) = a^{m + n}\\\\\bigstar\:\:\sf\dfrac{1}{a^n} = a^{-n}\\\\\bigstar\:\:\sf\sqrt[\sf n]{\sf a} = (a)^{\dfrac{1}{n}}\end{cases}}[/tex]